Face-selective regions show invariance to linear, but not to non-linear, changes in facial images. (December 2016) - Baseler, Heidi A.; Young, Andrew W.; Jenkins, Rob; Mike Burton, A.; Andrews, Timothy J.
Abstract: Familiar face recognition is remarkably invariant across huge image differences, yet little is understood concerning how image-invariant recognition is achieved. To investigate the neural correlates of invariance, we localized the core face-responsive regions and then compared the pattern of fMR-adaptation to different stimulus transformations in each region to behavioural data demonstrating the impact of the same transformations on familiar face recognition. In Experiment 1, we compared linear transformations of size and aspect ratio to a non-linear transformation affecting only part of the face. We found that adaptation to facial identity in face-selective regions showed invariance to linear changes, but there was no invariance to non-linear changes. In Experiment 2, we measured the sensitivity to non-linear changes that fell within the normal range of variation across face images. We found no adaptation to facial identity for any of the non-linear changes in the image, including to faces that varied in different levels of caricature. These results show a compelling difference in the sensitivity to linear compared to non-linear image changes in face-selective regions of the human brain that is only partially consistent with their effect on behavioural judgements of identity. We conclude that while regions such as the FFA may well be involved in the recognition of face identity, they are more likely to contribute to some form of normalisation that underpins subsequent recognition than to form the neural substrate of recognition per se. Highlights: Recognition is affected by linear but not non-linear changes in face. fMR-adaptation to identity shows invariance to linear changes in faces. fMR-daptation to identity is not invariant to non-linear changes in the identity. These findings shed light on the neural representation in face regions.